Genetic Diversity, Genetic Structure, and Demographic History of Giant Honeybee Apis dorsata Fabricius, 1793 (Hymenoptera: Apidae) in Thailand - Sopaladawan, Piyamas Nanork; Buala, Siripan; Pramual, Pairot (Tropical Natural History, 2024)
Giant honeybee (Apis dorsata Fabricius, 1793) is native to Asia. It is an efficient pollinator contributing to ecosystem stability. Populations of A. dorsata have been decreasing continuously due to various factors; however, information on genetic diversity is very limited. Therefore, purposes of this study were to assess the genetic diversity, structure, and demographic history of A. dorsata based on the mitochondrial cytochrome c oxidase I (COI) sequences. Adult worker bees from 41 colonies were collected throughout Thailand. In addition, 24 COI sequences of A. dorsata from other countries available in public databases were also incorporated into the data analysis. Overall, high haplotype (0.958) and low nucleotide diversities (0.00536) with a maximum intraspecific genetic divergence of 1.65% were found within Thai specimens. Population pairwise FST revealed genetically significant differences among Northern, Central and Southern populations while those from Northeastern are not. Median-joining network analysis revealed a star-like shape, a characteristic of the recent expanding population. This is supported by unimodal mismatch distribution and significantly negative of Tajima’s D and Fu’s Fs tests. Population expansion time is estimated to be 83,000 – 177,000 years ago, possibly in response to interglacial Pleistocene climatic fluctuation.